Ukraine Situation: Regional Refugee Response Plan - January-December 2024 - United Nations High Commissioner for Refugees (United Nations, 2024)
The war in Ukraine has been the fastest growing and largest displacement crisis in Europe since World War II and has precipitated a regional refugee response of commensurate scale. In the nearly two years since the Russian Federation’s large-scale invasion of Ukraine in February 2022, the flow of refugees into neighbouring countries, and beyond, has been met by a remarkable mobilization of assistance – by national and municipal authorities, civil society actors, local volunteers, and refugees themselves, all contributing to ensure protection and meet the essential needs of those fleeing violence. As the refugee response enters its third year in 2024, it continues to address significant needs in host countries, demonstrating an evolving and prolonged situation. Notably, this iteration of the plan reflects the overall ownership of the response and greater investment by host governments in the socio-economic inclusion of refugees.